Intergenus Protoplast Fusion between Pichia manshurica and Rhodosporidium paludigenum to Increase the Production of Inulinase - Wijanarka, Wijanarka; Soetarto, Endang Sutariningsih; Dewi, Kumala; Indrianto, Ari (UI Scholars Hub, 2014)
The purposes of this study was to identify the optimum concentration of the lytic enzyme Glucanex for protoplast isolation and to conduct fusion for the purpose of increasing inulinase production. The study performs the protoplast fusion technique using Pichia manshurica and Rhodosporidium paludigenum. Protoplast fusion consists of a series of stages: protoplast isolation, protoplast fusion, protoplast regeneration, and analysis of hybrid fusion results. Protoplast isolation and fusion success rate are determined by various factors, including age of the culture, media type, and type of lytic enzymes used. Hybrid results were analyzed using a fungicide as a marker and measuring specific growth rate (µ) of the hybrid compared with parental growth rates. Results demonstrated that a concentration of 4 mg/mL of Glucanex produces the greatest number of protoplasts, 7.2 x 1010 (cell/mL) for P. manshurica and 8.8 x 1010 (cell/mL) for Rh. paludigenum. The results of analysis of hybrid fusions indicate that the study has identified a new fusant, called fusant F4. Fusant F4 is capable of producing the highest inulinase, 0.6892 IU, compared with parentals P. manshurica, 0557 IU, and Rh. paludigenum, 0.3263 IU. Fusant F4 has specific growth rate (µ) of 0.3360/h and generation time (g) of 2.0629 h.